Implementasi PERMENDESAPDTTRANS NO. 2 Tahun 2016 Terkait Status Desa di Desa Sukarara Lombok Tengah - Siti Sriningsih; Endang Astuti; Baiq Ismiwati (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
Village development or village development is an effort to improve the welfare of the village community, this is stated in PermendesaPDTTrans N0 2 of 2016 related to the Village Build Index (IDM). The Village Development Index (IDM) will determine 5 village statuses, which are called several village classifications. The classification in question is an independent village, developed village, developing village, underdeveloped village, very left behind village. The purpose of this study was to analyze the implementation of Permen No 2 2016 related to the status of the Village in Sukarara Village, Lombok Tengah. This type of research is quantitative descriptive. Interview data collection techniques and library research (Research library). The research results obtained are Sukarara Lombok Tengah Village statuses included in the classification of Underdeveloped Villages. IDM composite calculation results 0.489 which means that the village has the potential social, economic, and ecological resources but has not been managed or lacked in efforts to improve the welfare and quality of human life.